2021
DOI: 10.1111/cas.14891
|View full text |Cite
|
Sign up to set email alerts
|

Novel knock‐in mouse model for the evaluation of the therapeutic efficacy and toxicity of human podoplanin–targeting agents

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…However, we previously found that a high-dose single administration (100 mg/kg) of 2F7 surrogate anti-monkey PDPN antibody harboring PG4D2-like neutralizing activity did not demonstrate acute toxicity in cynomolgus monkeys ( 33 ). Moreover, we confirmed that there was no toxicity or change in hematologic and biochemical parameters after repeated PG4D2 administration in Pdpn KI/KI mice expressing human/mouse chimeric PDPN in which the mouse PLAG4 domain was replaced with the human homologous PLAG4 domain ( 28 ).…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…However, we previously found that a high-dose single administration (100 mg/kg) of 2F7 surrogate anti-monkey PDPN antibody harboring PG4D2-like neutralizing activity did not demonstrate acute toxicity in cynomolgus monkeys ( 33 ). Moreover, we confirmed that there was no toxicity or change in hematologic and biochemical parameters after repeated PG4D2 administration in Pdpn KI/KI mice expressing human/mouse chimeric PDPN in which the mouse PLAG4 domain was replaced with the human homologous PLAG4 domain ( 28 ).…”
Section: Resultssupporting
confidence: 69%
“…S1; ref. 28 ). We also assessed PDPN expression in osteosarcoma cell lines obtained from samples surgically resected from patients with osteosarcoma after obtaining informed consent (Sa-xeno-147-P0 and GCB53-G3; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to OSCC, PDPN promotes a variety of other cancers including mammary carcinoma [ 62 , 63 ], glioma [ 64 67 ], melanoma [ 59 , 68 , 69 ], ovarian cancer [ 70 ], and pulmonary adenocarcinoma [ 71 73 ]. Indeed, PDPN has been identified as an enticing target for chemotherapy [ 74 , 75 ]. The roles of cadherins and PDPN in contact normalization described in this study should yield insight into fundamental mechanisms that affect the general process of cancer development and progression at the cellular level of the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Not only does this double the effort required for antibody discovery, but depending on the antibody fine epitope specificity, the impact of the antibody on disease in the different model systems may not be identical. This has been a challenge in developing antibodies to bind mouse CD3 to evaluate T cell retargeting antibodies and to evaluate antibody therapeutics to treat pediatric medulloblastoma in mice (43)(44)(45). In support of this future effort for myocilin, 2H2 has similar (within ~50%) K D values for each homolog and can easily be expressed with mouse or human constant domains to faithfully engage host Fc receptors (Table 3).…”
Section: Discussionmentioning
confidence: 99%